General Principles of Radiation Protection in Fields of Diagnostic Medical Exposure - Do, Kyung-Hyun (J Korean Med Sci, 2016)
After the rapid development of medical equipment including CT or PET-CT, radiation doses from medical exposure are now the largest source of man-made radiation exposure. General principles of radiation protection from the hazard of ionizing radiation are summarized as three key words; justification, optimization, and dose limit. Because medical exposure of radiation has unique considerations, diagnostic reference level is generally used as a reference value, instead of dose limits. In Korea, medical radiation exposure has increased rapidly. For medical radiation exposure control, Korea has two separate control systems. Regulation is essential to control medical radiation exposure. Physicians and radiologists must be aware of the radiation risks and benefits associated with medical exposure, and understand and implement the principles of radiation protection for patients. The education of the referring physicians and radiologists is also important.